(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Plastic is one among the foremost versatile materials of our fashionable age and however the recognition of plastic is that the drawback. “Wastes are not always waste if it’s separated as it was”. World is facing COVID-19 dangerous state of affairs and due to this people has started using individual plastic bottle that has led to increment of plastic waste and making waste management drawback, unknowingly. So, to resolve this problem, an innovative plan to style a system is employed that may store the used bottle of drinks and beverages. It’s a capability to store those bottles in predefined individual storage andreturns points to consumer as a reward. The aim of this paper is to gift the thought of plastic vending machine that is planned to function an answer to the matter of pollution caused because of plastic things particularly plastic bottles, that are normally used for storing cold drink, fruit juices etc. This paper proposes an Automation of plastic Waste material Segregation.It can be designed to sort the trash into metallic waste and plastic waste ready to be processed separately for the next process of operation. Once plastic is detected the consumer will be rewarded with points.